Breast Cancer Presenting as Unilateral Arm Edema - Zakaria, Shaheen (Springer-Verlag, 2007)
CONTEXT: Symptomatic arm lymphedema as the presenting symptom of invasive breast carcinoma is a rare occurrence. DESIGN: We report a case of invasive breast cancer presenting with unilateral arm swelling. The patient was initially thought to have venous thrombosis. A thorough physical examination and a mammogram revealed the presence of breast cancer and associated subclinical axillary lymphadenopathy. CONCLUSION: Failure to recognize this presentation can lead to misdiagnosis or a significant delay in diagnosis and treatment.